Metabolic engineering probiotic yeast produces 3S, 3′S-astaxanthin to inhibit B16F10 metastasis. (January 2020) - Tseng, Chung-Chih; Lin, Yu-Ju; Liu, Wangta; Lin, Hao-Yeh; Chou, Hsin-Yu; Thia, Caroline; Wu, Jou Hsien; Chang, Jo-Shu; Wen, Zhi-Hong; Chang, Jui-Jen; David Wang, Hui-Min
Abstract: 3S, 3′S-Astaxanthin is the most powerful antioxidant to scavenge free radicals in the world. In this study, a 3S, 3′S-astaxanthin biosynthesis pathway was constructed in a probiotic yeast, Kluveromyces marxianus, denoted YEAST, and its bioactive metabolites were extracted for biofunctional assessments. The bio-safety examination was achieved by two animal models as following: First, no significant toxic effects on YEAST groups were found in zebrafish; Second, after feeding YEAST for 4 weeks, the rat-groups showed no visible abnormality, and no significant change of the body weight and blood biochemistry tests. The inhibition of lung metastasis of melanoma cells and the increment of the survival rate were demonstrated by feeding YEAST and injecting the intravenous commercial astaxanthin in vivo rodent model. Based on in vitro assays of 1, 1-diphenyl-2-picryl-hydrazyl (DPPH) scavenging analysis, ferrous ion chelating ability, reducing power assessment, and mushroom tyrosinase inhibition evaluation, YEAST -astaxanthin showed anti-oxidative and tyrosinase suppressive properties. Taken together, the 3S, 3′S-astaxanthin producing probiotic yeast is safe to be used in the bio-synthesis of functional and pharmaceutical compounds, which have broad industrial applications on cosmetic, food and feed additive and healthcare. Highlights: A novel method produces astaxanthin by using yeast Kluveromyces marxianus ( YEAST ) to increase productivity. YEAST-a staxanthin is non-toxic in cellular based assay, zebrafish and mice platforms. YEAST-a staxanthin has effort on melanoma metastasis inhabitation in lung.